2014
DOI: 10.2108/zs140126
|View full text |Cite
|
Sign up to set email alerts
|

“Double-Trick” Visual and Chemical Mimicry by the Juvenile Orchid MantisHymenopus coronatusused in Predation of the Oriental HoneybeeApis cerana

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The use of allomones is primarily known from predator-prey systems, where predators lure prey animals with imitations of prey specific pheromones (e.g. [ 41 , 42 ]). This would be the case (in the opposite direction) if H .…”
Section: Discussionmentioning
confidence: 99%
“…The use of allomones is primarily known from predator-prey systems, where predators lure prey animals with imitations of prey specific pheromones (e.g. [ 41 , 42 ]). This would be the case (in the opposite direction) if H .…”
Section: Discussionmentioning
confidence: 99%
“…Hymenopus’ floral simulation alone is so convincing that they attract more insect pollinators than sympatric flowers13. Amazingly, nymphs of Hymenopus even emit allelochemicals that mimic intraspecific pheromone communication of the oriental honeybee Apis cerana Fabricius, 1793 as a deceptive predatory tactic16. Although adult female Hymenopus and Helvia ecologies have not been researched, the continued expression of the morphological pollinator attracting features8 and preferential feeding on pollinating insects16 indicates that they conserve the strategy.…”
mentioning
confidence: 99%
“…O'Hanlon et al, 2014a) by their bodies resembling a flower blossom (O'Hanlon et al, 2014b). Juvenile orchid mantises also emit volatile chemicals that attract honeybees (Mizuno et al, 2014). Although adult orchid mantises show no preference for inhabiting flowers over leafy vegetation (O'Hanlon et al, 2015) and juveniles are found on leaves more frequently than on flowers (Mizuno et al, 2014), they likely benefit from increased insect activity when they are near flowers (O'Hanlon et al, 2015).…”
Section: Encountering Preymentioning
confidence: 99%